Scaling of xylem and phloem transport capacity and resource usage with tree size - Hölttä, Teemu; Kurppa, Miika; Nikinmaa, Eero (Frontiers in Plant Science, 2013)
Xylem and phloem need to maintain steady transport rates of water and carbohydrates to match the exchange rates of these compounds at the leaves. A major proportion of the carbon and nitrogen assimilated by a tree is allocated to the construction and maintenance of the xylem and phloem long distance transport tissues. This proportion can be expected to increase with increasing tree size due to the growing transport distances between the assimilating tissues, i.e. leaves and fine roots, at the expense of their growth. We formulated whole tree level scaling relations to estimate how xylem and phloem volume, nitrogen content and hydraulic conductance scale with tree size, and how these properties are distributed along a tree height. Xylem and phloem thicknesses and nitrogen contents were measured within varying positions in four tree species from Southern Finland. Phloem volume, nitrogen amount and hydraulic conductance were found to be concentrated towards the branch and stem apices, in contrast to the xylem where these properties were more concentrated towards the tree base. All of the species under study demonstrated very similar trends. Total nitrogen amount allocated to xylem and phloem was predicted to be comparable to the nitrogen amount allocated to the leaves in small and medium size trees, and to increase significantly above the nitrogen content of the leaves in larger trees. Total volume, hydraulic conductance and nitrogen content of the xylem were predicted to increase faster than that of the phloem with increasing tree height in small trees (